Penguatan Kesadaran Spasial dan Literasi Pesisir: Siswa SMAN 1 Siantan Belajar Dinamika Abrasi dan Akresi Pantai Mempawah - Novita Sariani; Mustofa; Wiwik Cahyaningrum; Suherdiyanto; Norsidi; Ivan Veriansyah; Agus Suwarno; Ihsan Nurhakim (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Coastal areas are dynamic environments that are highly susceptible to changes caused by geomorphological processes, particularly coastal abrasion and accretion. Limited coastal literacy and students' spatial awareness of coastal dynamics often constrain understanding of shoreline changes and the importance of sustainable coastal environmental management. This condition served as the basis for implementing a Community Service Program (PKM) aimed at strengthening coastal literacy and enhancing students' spatial awareness through field-based geography learning on the dynamics of coastal abrasion and accretion at Mempawah Beach. The learning activities employed interactive lectures, group discussions, field observations, identification of abrasion and accretion landforms, shoreline change observations, and the completion of student worksheets (LKPD). The program was evaluated descriptively through field observations, group discussions, and an analysis of students' worksheet responses without employing pre-test or post-test assessments. The results indicate that the participants were able to recognize the characteristics of coastal abrasion and accretion based on geomorphological features observed in the field, identify factors influencing shoreline changes, and explain the relationship between natural processes and human activities in shaping coastal dynamics. Furthermore, the field-based learning activities provided meaningful contextual learning experiences that promoted the development of coastal literacy, spatial thinking skills, and environmental awareness regarding coastal conservation and mitigation efforts. Therefore, field-based geography learning can be considered an effective approach to strengthening students' coastal literacy and spatial awareness through direct interaction with real-world coastal environments, thereby fostering long-term environmental stewardship and sustainable coastal conservation attitudes.